Study of SMS security as part of an electronic voting system - Mushfiqur Rahman, Chowdhury; Khan, Shah Md. Adnan (BRAC University, 2010)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2006.